Reflection of Neo-Platonism on the Philosophy of MullÁ SadrÁ - Muhammad Mehdi GurjÐyÁn; Narjis RÙdgar (حکمت اسرا, 2012)
Plotinus was a major philosopher of the ancient Greek whose Enneads had a significant influence upon the Islamic philosophy. Among Muslim philosophers, MullÁ ÑadrÁ has greatly benefited from his views and doctrines, so that a good deal of specific theories of the Transcendent Philosophy (al-Îikmat al-MutaÝÁliya) have their roots in Plotinus’ views. Some of his views are: belief in the hierarchical degrees of being, the principle of ‘the simple reality is all things’, the principle of The One (al-WÁÎid), belief in the hierarchical degrees of the soul, the existential degrees in the human soul, and the belief in the presence of the whole material existents in transcendental world etc. However, what are the differences and similarities of the two Neoplatonic and Sadrian systems? By presenting the essential views and doctrines of the philosophy of Plotinus and MullÁ ÑadrÁ, this study seeks to show notable similarities and dissimilarities of the two systems. One of the consequences of this comparison is to understand and discover the extent of which the Transcendent Philosophy is influenced by Plotinus’ philosophy.